The Determinants of Commitment Escalation (Experimental Study: Covid-19 Pandemic as A Contextual) - Dyna Rachmawati; Patricia Felin Budianto (UNIB Press, 2022)
Managers play an important role in making the right decisions so that the company can survive and face unexpected situations such as the Covid-19 pandemic. This pandemic has left many business sectors struggling to survive hence managers need to make the right decisions according to current situations. A wrong decision can be caused by the action of a manager who justifies the decisions that havehave been made such as increasing their commitment to a project that has indicated failure. This can be referred to as commitment escalation or a person's tendency to continue a project despite the potential for failure. This study aims to determine the effect of adverse selection, framing, and the implementation of reward and punishment systems on the escalation of commitment by including the context of the Covid-19 pandemic. This study is experimental research with a 2x2x2 between and within subject design in the form of case problems distributed to undergraduate students majoring in accounting at Widya Mandala Catholic University Surabaya who have taken management accounting and financial management courses. The data obtained were processed using the ANOVA or Analysis of Variance. The results of this study indicate that adverse selection has marginally significant on commitment escalation. Framing has an impact on commitment escalation. Negative framing promotes higher commitment escalation than positive framing. The implementation of reward and punishment has no impact on commitment escalation. The implication of this study is framing plays an important role toward commitment escalation during the covid-19 pandemic. Managers have to seek positive information rather than negative information to make investment decisions during the covid-19 pandemic, to reduce commitment escalation.